Biological nitrification inhibition by rice root exudates and its relationship with nitrogen‐use efficiency. Issue 3 (13th June 2016) - Sun, Li; Lu, Yufang; Yu, Fangwei; Kronzucker, Herbert J.; Shi, Weiming
Summary: Microbial nitrification in soils is a major contributor to nitrogen (N) loss in agricultural systems. Some plants can secrete organic substances that act as biological nitrification inhibitors (BNIs), and a small number of BNIs have been identified and characterized. However, virtually no research has focused on the important food crop, rice ( Oryza sativa ). Here, 19 rice varieties were explored for BNI potential on the key nitrifying bacterium Nitrosomonas europaea . Exudates from both indica and japonica genotypes were found to possess strong BNI potential. Older seedlings had higher BNI abilities than younger ones; Zhongjiu25 (ZJ25) and Wuyunjing7 (WYJ7) were the most effective genotypes among indica and japonica varieties, respectively. A new nitrification inhibitor, 1, 9‐decanediol, was identified, shown to block the ammonia monooxygenase (AMO) pathway of ammonia oxidation and to possess an 80% effective dose (ED80 ) of 90 ng μl −1 . Plant N‐use efficiency (NUE) was determined using a 15 N‐labeling method. Correlation analyses indicated that both BNI abilities and 1, 9‐decanediol amounts of root exudates were positively correlated with plant ammonium‐use efficiency and ammonium preference. These findings provide important new insights into the plant–bacterial interactions involved in the soil N cycle, and improve our understanding of the BNI capacity of rice in the context of NUE.